An integrated method for designing user interfaces based on tests. - Schilling, Albert (Software engineering notes.)
We present artifacts and techniques used for User Interface (UI) evaluation, performed by professionals from the Human-Computer Interaction (HCI) area of study, covering Usability and Semiotic Engineering, which can assist Software Engineering (SE) to perform usability tests earlier. The study of various interaction alternatives, made possible by these artifacts, verifies if they are in accordance with users' preferences and constraints, and usability patterns, and can enhance the probability of achieving a more usable and reliable product.